EFFECT OF FE3O4/SIO2/TIO2 PHOTOCATALYST ON POLLUTANT MANAGEMENT IN SWAMP WATER - Liasari, Beta Riana; Arsyad, Fitri Suryani; Assaidah, Assaidah; Ramlan, Ramlan; Nur’aini, Siti; Soerya, Balada (Indonesian Physical Review, 2024)
Water is an essential source of life, thus regulating its purity is critical in daily living. Water has a high acid content (pH) and contains a variety of harmful chemical elements such as iron (Fe), copper (Cu), sulphate (SO4), nitrate (NO3), chloride (Cl), and other dangerous bacteria. The goal of this research is to create wastewater management such that it can be used by the community. The process involves creating Fe3O4 catalysts that have been modified using SiO2 and TiO2. The application of dirty water employs Fe3O4/SiO2/TiO2 to bind contaminants in polluted water. The results of the photocatalyst process carried out by Fe3O4/SiO2/TiO2 reach 90% in 180 minutes of UV light irritation so that it can degrade water pollutants such as methylene orange.